Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Pasien Pre Anestesi dengan Tindakan Spinal Anestesi Di RS Jatiwinangun Purwokerto - Chaerunisa, Siti Bakhittah; Yudha, Magenda Bisma; Amelia Andini (Pusat Riset dan Inovasi Nasional, 2026)
Pre-anesthetic anxiety is a psychological problem commonly experienced by patients before undergoing surgery with spinal anesthesia. This condition can cause both physiological and psychological impacts if not properly managed. Family support serves as an important external factor that helps reduce patient anxiety. This study aimed to determine the relationship between family support and anxiety levels among pre-anesthetic patients undergoing spinal anesthesia at Jatiwinangun Hospital, Purwokerto. This research used a quantitative approach with a cross-sectional design. The sample consisted of 43 respondents selected using a total sampling technique. Research instruments included a family support questionnaire and the Hamilton Rating Scale of Anxiety (HARS). Data were analyzed using the Spearman Rank test with a significance level of 0.05. The results showed that most respondents with good family support had lower anxiety levels compared to those with poor family support. The Spearman Rank test obtained a p-value of 0.00 (<0.05) and a correlation coefficient of r = 0.230, indicating a significant relationship with a low correlation strength. Optimal family support can serve as a non-pharmacological intervention to reduce patient anxiety before surgery.